Visibility and Effectiveness of PJOK Learning in Junior High Schools in Buleleng District - I Wayan Restu Adi Wiguna; I Gede Suwiwa; I Ketut Yoda (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2024)
Sports and health physical education involves physical activity for students which aims to improve fitness, improve students' motor skills, healthy living behavior, and foster sportsmanship. The aim of this research was to determine the visibility and effectiveness of PJOK learning in junior high schools (SMP) throughout Buleleng Regency. This type of research is descriptive - quantitative with data collection techniques namely 1) Survey, 2) Observation, 3) Documentation study, and 4) Interview. The sample used in this research was 46 schools from a population of 72 schools. The results of this research show the first two results in terms of learning visibility, namely that the personality competency score is 7.05 in the "Good" category, learning activities are 7.39 in the "Good" category, and learning implementation plans are 6.85 in the "Good" category while the secondly, in terms of learning effectiveness, the students' grades show that all are above the minimum completeness criteria, so the students have followed PJOK learning well, and seen from the questionnaire given to the number of respondents, 128 people with 12 questions, getting the average percentage in the figure. 81.28% of the results show that the effectiveness of PJOK learning in junior high schools (SMP) in Buleleng Regency is categorized as very effective